Effect of Directed Activities Related to Texts on English Skill: Relevance and Adequacy of the Content of Grade XI Students - Abdul Rauf, Muhammad Saeed, (PJE, 2023)
The study was aimed to find out the effect of directed activities related to texts (DARTs) on English writing skill: Relevance and adequacy of the contents. An experimental study was conducted through pre-test post-test control group design. A public sector degree college for boys from district Lahore was selected as sample of the study. Sixty students out of 400 enrolled in the session 2018-19 were selected and divided into two equal groups randomly. Study intervention period was of 16 weeks